On the role of heuristics: Experimental evidence on inflation dynamics - Johann Graf Lambsdorff; Manuel Schubert; Marcus Giamattei (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2011)
We carry out an experiment on a macroeconomic price setting game where prices are complements. Despite relevant information being common knowledge and price flexibility we observe significant deviation from equilibrium prices and history dependence. In a first treatment we observe that equilibrium values were obtained in the long run but at the cost of a very slow adjustment and thus history dependence. By reporting a business indicator in a simpler form, subjects were given the chance to coordinate their prices by help of a heuristic in a second treatment. This option was widely taken, bringing about excess volatility and a deviation from equilibrium even in the long run. In a third treatment with staggered pricing we observe, contrary to theoretical predictions, the one-round ahead (publicly known) shock is significant, but future inflation is not. Our findings cast light on price dynamics when subjects have limited computational capacities.
Keywords: E31; C92; 330; Inflation Persistence; Staggered Prices; Sticky Reasoning; New Keynesian Phillips Curve